Environmental Management System in Verdegreen Hotel - João Pessoa/PB: A Case Study under the Perspective of Resource-Based View - Salgado, Camila Cristina Rodrigues (2015)
The pressure for a new pattern of sustainable development has required of modern organizations the search for competitiveness, but respecting and considering environmental issues.  In this sense, a tool that acts in the implementation of structured strategies is the Environmental Management System (EMS), which focuses on improving environmental performance. This improvement, in turn, can generate to the organizations many benefits , among which, obtaining competitive advantages, susceptible of measurement from different perspectives. One of these is the application of VRIO model, reasoned by the Resource-Based View (RBV), which considers that differences between companies occurs due to differences between its internal resources and capabilities. However, although was been found some studies in the literature that evaluate the competitive potential of certain organizations , such assessments are not performed on specific objects, like the SEM’s. Thus, the aim of this study was to evaluate the resources and capabilities (environmental strategies) adopted by the SGA of the Verdegreen Hotel, identifying which of these have the potential to generate competitive advantage. For this, this exploratory-descriptive character study and delineated as field research and case study was used as data collection tools: a literature survey, semi-structured interviews, document research and direct observation. The interpretation of results and consolidation of information were conducted from a qualitative approach, using two techniques of data analysis, namely: content analysis and analysis through VRIO model. The results show that the hotel is quite structured in relation to their EMS, as well as reaching related to improving the management of environmental factors, strengthening the image and gains in competitiveness benefits. On the other hand, the main difficulties for the implementation of the system are related to employees and suppliers. With regard to environmental strategies adopted, of the 25 strategies identified, 10 showed the potential to generate competitive advantage.